2010
DOI: 10.1161/circulationaha.109.894543
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Long-Term Major Vascular Events and Resource Consumption in Patients Receiving Off-Pump Coronary Artery Bypass

Abstract: Background-Despite its widespread use and short-term efficacy, substantial uncertainty remains about the long-term outcomes and cost-effectiveness of off-pump coronary artery bypass (OPCAB). Methods and Results-A retrospective review of prospectively collected data was conducted of 6665 consecutive patients undergoing isolated coronary artery bypass graft (CABG) at our institution during 1999 to 2006. All patients were followed up until September 30, 2008. Short-and long-term outcomes were compared between OPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 24 publications
(27 reference statements)
1
33
2
Order By: Relevance
“…In a randomized study comparing off-pump and on-pump CABG, the mean total hospitalization cost per patient was $2272 less for off-pump CABG at hospital discharge and $1955 less at 1 year. 1248 Another study of 6665 patients who underwent CABG between 1999 and 2005 determined that off-pump CABG provided a small short-term gain, 1249 although off-pump patients had increased long-term risks of repeat revascularization and major vascular events, especially if they were considered to be high risk. In the long run, in fact, off-pump patients utilized more resources.…”
Section: Cost-effectiveness Of Cabg and Pcimentioning
confidence: 99%
“…In a randomized study comparing off-pump and on-pump CABG, the mean total hospitalization cost per patient was $2272 less for off-pump CABG at hospital discharge and $1955 less at 1 year. 1248 Another study of 6665 patients who underwent CABG between 1999 and 2005 determined that off-pump CABG provided a small short-term gain, 1249 although off-pump patients had increased long-term risks of repeat revascularization and major vascular events, especially if they were considered to be high risk. In the long run, in fact, off-pump patients utilized more resources.…”
Section: Cost-effectiveness Of Cabg and Pcimentioning
confidence: 99%
“…A higher repeat revascularization rate after offpump CABG has also been found in other large nonrandomized trials. 22,23 As noted in a recent editorial, surgeons continue to fear incomplete revascularization with off-pump CABG, and anastomotic performance may be the Achilles heel of off-pump surgery. 24 Incomplete or ineffective revascularization was associated with worse cardiovascular outcomes at 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent prospective observational analysis, Hu et al showed a statistically significant increase in long-term major cardiovascular events with OPCAB compared with ONCAB (43.8% vs. 41.2%, P=0.002), although the absolute difference was small. 78 Long-term repeat revascularization (9.4% vs. 7.6%, P=0.03), recurrent angina (39.0% vs. 26.9%, P<0.001), and cardiovascular disease-related hospitalization (56.5% vs. 41.6%, P<0.0001) were all significantly higher with OPCAB compared with ONCAB.…”
Section: Graft Patency and Repeat Revascularizationmentioning
confidence: 89%